Psychoeducation at initial phase of treatment for patients with obsessive compulsive disorder and their families - Mukai, Keiichiro; Matsunaga, Hisato (Anxiety Disorder Research, 2024)
Obsessive compulsive disorder (OCD) is a psychiatric disorder characterised by intrusive thoughts (obsession) and repetitive behaviors (compulsion). Selective serotonin reuptake inhibitors, cognitive behavioral therapy and their combination therapy are endorsed first line treatments, although only two SSRIs are approved for OCD and the dissemination of CBT (cognitive behavioral therapy) is not yet widespread. Treatment for OCD tends to be prolonged, but achieving complete remission within two years of initiating treatment is desirable to prevent relapse and recurrence. Psychoeducation in the early stages of treatment is considered one of the most crucial interventions for overall therapeutic success. This review begins with a case presentation, followed by a comprehensive review of psychoeducation in the early stages of OCD treatment, focusing on its pivotal role in enhancing treatment outcomes.